Denial Is The Killer and Other Stories. - Charles Nfon (Langaa RPCIG, 2016)
There is no denying the havoc HIV/AIDS has wrecked around the globe. The worst impact is seen in the developing world and in impoverished communities in the developed world. However, being HIV positive is not a death sentence. Why then do many still die from it? Denial is the Killer is a fictionalisation of the reality on why and how the persisting vestiges of HIV/AIDS devastation can be stopped.